Podejście umiarkowane w sporze o możliwość i użyteczność moralną kodyfikacji norm etycznych (Moderate Position in the Debate on the Moral Possibility and Usefulness of Ethical Standards Codification) - Andrzej Klimczuk (Annales. Ethics in Economic Life, 2014)
The popularisation of code elaboration addressed to various social groups is one of the features of the modern world. However, among researchers of this phenomenon a full consensus on the moral validity and usefulness of this activity does not exist. The article closely reviews the literature with regard to the reasons for the creation of a moderate position on the codification of ethical standards. The essay brings closer the main concepts of ethical codes and positions for their adoption and rejection. Attention is paid to ways of increasing the effectiveness of codes and the ethical decision-making procedure in a manner that undermines supporters and opponents of codification approaches. – – Popularyzacja tworzenia kodeksów zaadresowanych do różnych grup społecznych jest jedną z cech współczesnego świata. Wśród badaczy tego zjawiska nie ma jednak pełnej zgody na zasadność i użyteczność moralną tej działalności. Artykuł przybliża przegląd literatury przedmiotu w zakresie dotyczącym argumentów za stworzeniem umiarkowanego stanowiska na rzecz kodyfikacji norm etycznych. Przybliżono główne pojęcia dotyczące kodeksów etycznych i stanowiska za ich przyjęciem i odrzuceniem. Zwrócono uwagę na sposoby zwiększania skuteczności kodeksów oraz procedurę podejmowania decyzji etycznych w sposób godzący podejścia zwolenników i przeciwników kodyfikacji.
Keywords: M14; 330; professional ethics; codification; standardization; regulation of behaviour; situationism; social responsibility